REMOVAL OF PESTICIDES FROM SIMULATED WASTEWATER - Saini, Roli (My University, 2017)
Agriculture is the backbone of the economy in several countries, particularly India; therefore it is necessary to use pesticides for controlling pests. In India, the use of pesticides is high in some parts of the country in which, Andhra Pradesh (Seemandhra and Telangana) and Punjab consumes the largest amount of pesticides. Such high application of pesticides has resulted in an increase in the pesticide level in drinking water. There are many sources (water, fruit, vegetable, etc.) through which humans are exposed to pesticides which cause toxic effects on health. For this reason, it is very important to remove pesticides from water bodies.
Keywords: PESTICIDES; WASTEWATER